Kematangan Beragama Perspektif Al-Qur’an: Tafsiran Ayat Tematik Tentang Taqwa - Mukhlis, Zen Fuad; Syahidin, Syahidin; Kosasih, Aceng (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
The purpose of this study is to reveal the criteria for religious maturity from the perspective of the Koran. This research uses a qualitative approach and a descriptive method in the form of library research. Based on the research results, the Koran has a more comprehensive perspective regarding the personal criteria of a servant who has maturity in religion. The six characteristics of religious maturity offered by Gordon Allport existed in the Koran long before this Western concept was coined. More than that, every criterion of religious maturity contained in the Koran is not just a choice of religion but includes things that are ordered. Because Islam as a religion that makes the Koran in addition to the Sunnah a guideline for its people does not only demand obedience in the ritual order of worship, but the worship that is performed must be displayed in the form of everyday character that reflects a mature individual in his religion.